Mechanical and Hydric Stress Effects on Maize Root System Development at Different Soil Compaction Levels - de Moraes, Moacir Tuzzin; Debiasi, Henrique; Franchini, Julio Cezar; Bonetti, João de Andrade; Levien, Renato; Schnepf, Andrea; Leitner, Daniel (Frontiers in Plant Science, 2019)
Soil mechanical resistance, aeration and water availability directly affect plant root growth. The objective of this work was to identify the contribution of mechanical and hydric stresses on maize root elongation, by modelling root growth while taking the dynamics of these stresses in an Oxisol into consideration. The maize crop was cultivated under four compaction levels (soil chiselling, no-tillage system, areas trafficked by a tractor, and trafficked by a harvester), and we present a new model, which allows to distinguish between mechanical and hydric stresses. Root length density profiles, soil bulk density and soil water retention curves were determined for four compaction levels up to 50 cm in depth. Furthermore, grain yield and shoot biomass of maize were quantified. The new model described the mechanical and hydric stresses during growth for field data in maize crop or the first time. Simulations of root length density in 1D and 2D showed adequate agreement with the values measured under field conditions. Simulation makes it possible to identify the interaction between the soil physical conditions and maize root growth. Compared to the no-tillage system, grain yield was reduced due to compaction caused by harvester traffic and by soil chiselling. The root growth was reduced by the occurrence of mechanical and hydric stresses during the crop cycle, the principle stresses were mechanical in origin for areas with agricultural traffic, and water based in areas with soil chiselling. Including mechanical and hydric stresses in root growth models can help to predict future scenarios, and coupling soil biophysical models with weather, soil and crop responses will help to improve agricultural management.